2014
DOI: 10.1002/jhbp.131
|View full text |Cite
|
Sign up to set email alerts
|

STATs profiling reveals predominantly‐activated STAT3 in cholangiocarcinoma genesis and progression

Abstract: STAT3 is the major STAT, which plays roles in the inflammation that contributes to CCA carcinogenesis and progression and may serve as a marker for a poor prognosis of CCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 49 publications
2
37
0
Order By: Relevance
“…Since the proteins affected by metformin treatment, as observed in this study, can be mediated by NF-ĸB and STAT3, important transcription factors in carcinogenesis and progression of CCA (15,16), it was thus interesting to investigate whether metformin affected CCA cells via NF-ĸB or STAT3 pathways. The levels of NF-ĸB (p65) and STAT3 from whole-cell lysates of CCA cells treated with 10 and 20 mM metformin for 48 h and the control cells were determined using western blots.…”
Section: Metformin Inhibited Nuclear Localization Of Nf-ĸb and Stat3 mentioning
confidence: 89%
See 1 more Smart Citation
“…Since the proteins affected by metformin treatment, as observed in this study, can be mediated by NF-ĸB and STAT3, important transcription factors in carcinogenesis and progression of CCA (15,16), it was thus interesting to investigate whether metformin affected CCA cells via NF-ĸB or STAT3 pathways. The levels of NF-ĸB (p65) and STAT3 from whole-cell lysates of CCA cells treated with 10 and 20 mM metformin for 48 h and the control cells were determined using western blots.…”
Section: Metformin Inhibited Nuclear Localization Of Nf-ĸb and Stat3 mentioning
confidence: 89%
“…To investigate the alternative pathways in response to metformin treatment, NF-ĸB and STAT3, the major transcription factors reported in development and progression of liver fluke-associated CCA (15,16) were further examined. The results from western blots of whole-cell lysates showed no differences of p-STAT3 at both Y705 and S727 and the expression levels of p65 between the controls and the metformin-treated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies has indicated that CCA is caused by dysregulation of the tumor suppressor genes or oncogenes (Loilome et al, 2011;Namwat et al, 2012;Dokduang et al, 2014) However, the molecular mechanism(s) for CCA carcinogenesis remains unclear. Several studies have demonstrated that alteration of PI3K/AKT/PTEN and Wnt/ β-catenin was found in many cancers and these pathways may serve as the potential targets for cancer treatment (Gong et al, 2012;Pandurangan, 2013;Jannesari-Ladani et al, 2014;Tan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 plays important roles in the inflammation that contributes to carcinoma [36]. TAMs can decrease antigen presenting ability and promote the proliferation and growth of tumor cells [37].…”
Section: Tams and Breast Cancermentioning
confidence: 99%